Biothermoplastic elastomer (BTPE), influence of architecture on mechanical properties - Tjin, Monica Suryana. (2010)
Biodegradable thermoplastic elastomer was acquired by synthesizing four-armed and three-armed star-shaped copolymers via ring-opening polymerization with multifunctional initiator, such as pentaerythritol and glycerol, using stannous octoate (SnOct2) catalyst in bulk at 130oC. Random copolymer of PCL and PTMC serves as soft block and PLLA as hard block. The resulting star-shaped copolymers were characterized by 1H NMR, SEC, DSC, and INSTRON methods which provide structural, thermal, and mechanical properties of the copolymers. The mechanical properties of the star-shaped copolymers were determined by molar ratio of -CL and TMC. Microcrystalline regions present in the soft block as well as the amount of hard block have been found to play an important role in providing elastic properties to the star-shaped copolymers. These highly elastic star-shaped copolymers exhibit promising contribution to the emerging field of soft-tissue engineering.